Growth dynamics of tree-line and lake-shore Scots pine (Pinus sylvestris L.) in the central Scandinavian Mountains during the Medieval Climate Anomaly and the early Little Ice Age - Linderholm, Hans W.; Zhang, Peng; Gunnarson, Björn E.; Björklund, Jesper; Farahat, Emad; Fuentes, Mauricio; Rocha, Eva; Salo, Riikka; Seftigen, Kristina; Stridbeck, Petter; Liu, Yu (Frontiers in Ecology and Evolution, 2014)
Trees growing at their altitudinal or latitudinal distribution in Fennoscandia have been widely used to reconstruct warm season temperatures, and the region hosts some of the world’s longest tree-ring chronologies. These multi-millennial long chronologies have mainly been built from tree remains found in lakes (subfossil wood from lake-shore trees). We used a unique dataset of Scots pine tree-ring data collected from wood remains found on a mountain slope in the central Scandinavian Mountains, yielding a chronology spanning over much of the last 1200 years. This data was compared with a local subfossil wood chronology with the aim to 1) describe growth variability in two environments during the Medieval Climate Anomaly (MCA) and the early Little Ice Age (LIA), and 2) investigate differences in growth characteristics during these contrasting periods. It was shown that the local tree-line during both the MCA and early LIA was almost 150 m higher that at present. Based on living pines from the two environments, tree-line pine growth was strongly associated with mid-summer temperatures, while the lake-shore trees showed an additional response to summer precipitation. During the MCA, regarded to be a period of favourable climate in the region, the tree-ring data from both environments showed strong coherency and moderate growth variability. In the early LIA, the two chronologies were less coherent, with the tree-line chronology showing more variability, suggesting different growth responses in the two environments during this period of less favourable growing conditions. Our results indicate that tree-ring width chronologies mainly based on lake-shore trees may need to be re-evaluated.